2018
DOI: 10.1111/gcbb.12527
|View full text |Cite
|
Sign up to set email alerts
|

Does corn market uncertainty impact the US ethanol prices?

Abstract: The growing interest in biofuel as a green energy source has intensified the linkages between corn and ethanol markets, especially in the United States that represents the largest producing and exporting country for ethanol in the world. In this study, we examine the effect of corn market uncertainty on the price changes of US ethanol applying a set of GARCH-jump models. We find that the US ethanol price changes react positively to the corn market volatility shocks after controlling for the effect of oil price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
(66 reference statements)
3
18
0
Order By: Relevance
“…Our results, notably, are in line with earlier studies . These authors also document the evidence of significant jumps phenomena in energy and biofuel markets.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results, notably, are in line with earlier studies . These authors also document the evidence of significant jumps phenomena in energy and biofuel markets.…”
Section: Resultssupporting
confidence: 93%
“…For instance, unlike the conventional GARCH process, the jump process allows us to study the effect of anomalous information emanating from unpredictable circumstances. It can also successfully detect the jump behavior exhibited in the underlying price series . Modeling jumps is essential to recognize future price risks, so our study contributes to the scarce literature by further unfolding jump behavior in Brazilian ethanol market.…”
Section: Introductionmentioning
confidence: 84%
“…It can be thus concluded that oil price volatility has emerged as a driving force of US ethanol price changes. The findings of this empirical research are in line with previous studies, which also show that the US ethanol prices are driven by crude oil volatility and that oil volatility has a positive impact on US ethanol returns …”
Section: Resultssupporting
confidence: 91%
“…More specifically, previous researchers claim that biofuels have been brought into the energy markets as a substitute for fossil fuels in order to mitigate the volume of carbon emissions and minimize the adverse impact of oil price uncertainty . Given that oil market risk emerges as one of the driving forces of the ethanol market price changes, several researchers have investigated the effect of oil prices on the US ethanol markets …”
Section: Introductionmentioning
confidence: 99%
“…As far as we are aware, we are the first to examine whether the information content of the CIV index is convenient for predicting the realized volatility of the US ethanol market. However, a recent study used the CIV index to investigate whether corn volatility affected US ethanol market returns, whereas the current study examines the connections between the realized volatility of ethanol returns and the implied volatilities of the corn market. This study also examines the predictive capability of the CIV index.…”
Section: Introductionmentioning
confidence: 99%